Katokkon Pepper (Capsicum chinense Jacq.) Ploidy Determination by Morphological Characteristic and Flow Cytometry Analysis - Rinaldi Sjahril; Muh. Riadi; Ifayanti Ridwan Saleh; Ernitha A. Galla; Kasmiati Kasmiati; Nurhaya J. Panga; Novitasari Novitasari; A. R. Trisnawaty (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Katokkon pepper plant is originated from Toraja, South Sulawesi, Indonesia. This endemic pepper variety has unique hot and spicy characters with a distinctive bell pepper aroma, and aesthetic shape similar to paprika, but with smaller size. This research was conducted to identify ploidy level and plant morphology of colchicine induced Katokkon pepper at Laboratory of Plant Reproduction Bioscience and Biotechnology, Department of Agronomy, Faculty of Agriculture, Universitas Hasanuddin and experimental field of Agricultural Extension System Vocational High School Santo Paulus Tana Toraja (S 03Â°04â€™177â€ E 119Â°51â€™526â€). Two weeks old seedlings were immersed for 4.5 hours in colchicine concentration (0.00%, 0.0125%, 0.025%, 0.05% and 0.10%). Flow cytometry analysis was carried out using Partec Cy-Flow SpaceTM. Result showed that colchicine concentration (0.025%, 0.05% and 0.1%) produced mixoploid plants with two set of chromosomes (2n=24, 4n=48). This study also found morphological differences between mixoploids plants induced by 0.025%, 0.05% and 0.1% colchicine and diploid plants (0% and 0.0125% colchicine) during first two juvenile leaves phase. However, this difference did not occur further, and eventually morphology of adult mixoploid plant was not significantly different from control (diploid), which concurred to grading mixoploid grade 2. The mixoploid plants analyzed consist of higher diploids cells than tetraploid.